2011
DOI: 10.4103/0973-1482.92012
|View full text |Cite
|
Sign up to set email alerts
|

Bone invasion in oral cancer patients: A comparison between Orthopantamograph, conventional computed tomography, and single positron emission computed tomography

Abstract: The present study showed that SPECT was highly sensitive, but with a very low specificity due to an increase in false positive values. However, OPG and conventional CT showed an acceptable degree of sensitivity and specificity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 8 publications
1
7
0
1
Order By: Relevance
“…Plain radiography is not helpful in assessing soft tissues. It has been shown that the assessment of bone involvement on panoramic radiographs has a sensitivity of 75% and specificity of 100%, respectively [16]. …”
Section: Imaging Methods In Oral Cancermentioning
confidence: 99%
See 2 more Smart Citations
“…Plain radiography is not helpful in assessing soft tissues. It has been shown that the assessment of bone involvement on panoramic radiographs has a sensitivity of 75% and specificity of 100%, respectively [16]. …”
Section: Imaging Methods In Oral Cancermentioning
confidence: 99%
“…However, the changes seen in serial CT studies can give information regarding the underlying process. The sensitivity and specificity of detecting recurrence and assessing treatment response are 50% and 88% respectively [13,1618]. …”
Section: Imaging Methods In Oral Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…After retrieving the full text, 17 studies were included (Fig 1). [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] …”
Section: Results Of Search and Study Inclusionmentioning
confidence: 99%
“…Oral malignancies represent approximately 13% of all malignancies, thereby, translating into 30,000 new cases every year. 1 The majority 84-97% of oral malignancies are SCCs. 2 The countries of South Asian region including India, Pakistan, Bangladesh, Sri Lanka, Bhutan, Nepal, Iran and Maldives are particularly affected with oral cancer ranking either first or second with regard to different types of cancer prevalence in these countries.…”
Section: Introductionmentioning
confidence: 99%